A Case of Peutz-Jeghers Syndrome Presenting With an Inoperable Periampullary Tumor - UPRAK, TEVFİK KIVILCIM (CUREUS INC, 2021)
Peutz-Jeghers syndrome (PJS) is a syndrome characterized by multiple hamartomatous polyps in the gastrointestinal system and melanin pigments accumulating in the skin and mucous membranes. Patients with PJS have an increased risk of gastrointestinal malignancies. In this syndrome, pancreatic cancer is primarily detected in older ages. In this article, we present a case of a patient with an unresectable periampullary tumor and PJS.
Keywords: peutz-jeghers syndrome; periampullary tumors; gastric outlet obstruction